Analisis Nilai Deplesi Dari Produksi Hasil Hutan Di Kabupaten Tanah Laut - Aulia Rahmah; M. Anshar Nur (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
AbstractThis research aims to analyze the development of depletion value, PSDH revenue,and comparison of depletion value with PSDH from forest products production in TanahLaut Regency. Data collection techniques are documentation from previous research,online, and intentional surveys. Data is processed by mathematical calculations usingdepletion formula, then compared to PSDH revenue.The research results showed that ups and downs depletion value depended on thevolume of round wood. Depletion per unit of round wood production of natural forests ismore significant than plantation forests. The realization of PSDH received by TanahLaut Regency is smaller than PSDH, which should be accepted, about 28,73 percent.The depletion value of rounded wood is more significant than the PSDH amount wasreceived. PSDH value is only 1,55 percent of total round wood depletion (Rp.40.427.004.997,70).